Cavernous Angioma of the Corpus Callosum Presenting with Acute Psychosis. (5th March 2014) - Pavesi, Giacomo; Causin, Francesco; Feletti, Alberto
Abstract : Psychiatric symptoms may occasionally be related to anatomic alterations of brain structures. Particularly, corpus callosum lesions seem to play a role in the change of patients' behavior. We present a case of a sudden psychotic attack presumably due to a hemorrhagic cavernous angioma of the corpus callosum, which was surgically removed with complete resolution of symptoms. Although a developmental defect like agenesis or lipoma is present in the majority of these cases, a growing lesion of the corpus callosum can rarely be the primary cause. Since it is potentially possible to cure these patients, clinicians should be aware of this association.